The variation of intestinal autochthonous bacteria in cultured tiger pufferfish Takifugu rubripes - Gao, Lei; Zhang, Ziyang; Xing, Zhen; Li, Qingsong; Kong, Ning; Wang, Lingling; Song, Linsheng (Frontiers in Cellular and Infection Microbiology, 2022)
Intestinal autochthonous bacteria play important roles in the maintenance of the physiological homeostasis of animals, especially contributing to the host immune system. In the present study, the variation of autochthonous bacterial community in the intestinal tract of 2-7 months-old tiger pufferfish Takifugu rubripes and bacterial communities in the seawater of recirculating aquaculture system (RAS) and the following offshore sea cage aquaculture system (OSCS) were analyzed during the aquaculture period from May to October 2021. Proteobacteria was found to be the most dominant phyla in both intestinal and seawater bacterial communities, which accounted for 68.82% and 65.65% of the total bacterial abundance, respectively. Arcobacter was the most core bacterial taxon in the intestinal bacterial community, with the most dominant abundance (42.89%) at the genus level and dominant positions in co-occurrence relationships with other bacterial taxa (node-betweenness value of 150). Enterococcaceae was specifically enriched in the intestinal bacterial community of pufferfishes from RAS, while Vibrionaceae was enriched in the intestinal bacterial community from OSCS. The F-values of beta diversity analysis between intestinal and seawater bacterial communities generally increased from May (6.69) to October (32.32), indicating the increasing differences between the intestinal and seawater bacterial communities along with the aquaculture process. Four bacterial taxa of Weissella sp., Akkermansia muciniphila, Dietzia sp. and Psychrobacter pacificensis had significant correlations with immune response parameters, and they were suggested to be the indicators for immune status and pathological process of pufferfish. The knowledge about the specific core bacteria, potentially pathogenic bacteria and the change of bacterial community in the intestinal tract of cultured pufferfish is of great scientific significance and will contribute to the understanding of intestinal bacterial homeostasis and biosecurity practice in pufferfish aquaculture.